Inherited Hemoglobin Disorders - Munshi, Anjana (IntechOpen, 2015)
The book, Inherited Hemoglobin Disorders, describes the genetic defects of hemoglobins, disease complications, and therapeutic strategies. This book has two distinct sections. The first theme includes seven chapters devoted to the types of hemoglobinopathies, mutation spectrum, diagnostic methods, and disease complications, and the second theme includes three chapters focusing on various treatment strategies. The content of the chapters presented in the book is guided by the knowledge and experience of the contributing authors. This book serves as an important resource and review to the researchers in the field of hemoglobinopathies.